Unveiling English textbook tasks: Littlejohn's second-level analysis evaluation - Abdulali, Adim Muhammed Adim; Sacko, Makan; Sumekto, Didik Rinan (Universitas Sarjanawiyata Tamansiswa, 2023)
This research was conducted to reveal the book evaluation based on level 2 analysis by Littlejohn criteria. This research aims to (1) analyze to what extent tasks in the textbook “The 21st Century English for Libya Preparatory 2” meet one of the criteria of a good textbook suggested by Littlejohn and (2) discover the strengths and the weaknesses of the textbook used by eight graders of Junior High School in Libya. This study is qualitative research data that was collected by analyzing the textbook using Littlejohn criteria. The level 2 analysis by Littlejohn was used to analyze the textbook by doing a checklist. One unit was analyzed as the evaluation sample, and it was named Unit 1. Two major findings emerged from the research using this level of analysis. Firstly, the tasks in “The 21st Century English for Libya Preparatory 2” are categorized as a good element to support the book as a good book. Secondly, the research found both strengths in the textbook. The strengths were discovered in the book. Based on level 2 of analyses from Littlejohn, the research found both strengths to the textbook. Every unit has tasks stated by Littlejohn, except songs. They can encourage students to speak and share their ideas and experiences with their classes. However, in terms of weaknesses, most of the tasks are not balanced – still dominated by receptive skills, reading, and listening. In addition, the activities outside class are also still rare served by the textbook. Based on the results above, it can be inferred that this evaluation is truly important to be done to know the quality of the textbook as an important element in the teaching and learning process.